Criticism of Ivan Illich on the Schooling System: The Philosophical Contribution to Strengthening Education Outside School in Indonesia - Alim Harun Pamungkas (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
Ivan Illich's two main criticisms of schooling systems are the existence of schooling which is considered as a media determinant of human education and community apathy towards schooling. Ivan Illich has defined the schooling system as an age-specific, teacher-related process, requiring full-time attendance, at an obligatory curriculum. A school institution is defined as (1) a formal education institution intended for certain age levels, such as basic, middle, and upper; (2) full time learning the process; (3) having a compulsory curriculum as a standard for graduation and intelligence. According to Ivan Illich, education should be a practice of learning experiences for someone in his life. However, it was precisely the reduction of learning rights over the existence of a set of obligations at school. On the other hand, the existence of schools actually makes people passive towards education because of the assumption that schools are the determinant of the future. This condition generally occurs in low-income middle-class people who are too busy working to meet their daily needs. This condition raises a situation of resignation that parents and families are not obliged to have sufficient intelligence to accompany the intelligence process of their children.Keywords: Criticism, Ivan Illich, Philosophy, Non-Formal Education, Learning